Synthesis and structural characterization of CoxFe3−xC (0 ≤ x ≤ 0.3) magnetic nanoparticles for biomedical applications. (6th February 2019) - Gangwar, A.; Singh, G.; Shaw, S. K.; Mandal, R. K.; Sharma, A.; Meena, Sher Singh; Prajapat, C. L.; Prasad, N. K.
Abstract : The ferrofluids of pure and Co-substituted iron carbides exhibited heating abilities suitable for bioapplications. Abstract : Herein, cobalt-substituted iron carbide (Co x Fe3− x C, 0 ≤ x ≤ 0.3) magnetic nanoparticles (15–30 nm) were prepared by a sol–gel assisted route. X-ray diffraction (XRD) and electron diffraction patterns suggested that all the samples had a single phase structure. Furthermore, Mössbauer spectroscopy validated the monophasic nature of all the Co-substituted iron carbides, except for x = 0.3. The results of Mössbauer spectroscopy for this sample indicated the presence of the Fe–Co alloy along with the carbide phase. The saturation magnetization value was found to decrease with an increase in Co concentration ( x ≤ 0.16); however, it increased for the x = 0.3 sample due to the presence of a secondary phase (Fe–Co alloy). Ferrofluids of the pure and Co-substituted iron carbides in oleic acid exhibited good heating abilities during the magnetic hyperthermia experiment at different external fields.